Factors That Influence Nurses' Performance in Inpatients at the General Hospital Dr. Sayidiman Magetan - Markus M Mosse (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Nurses in providing nursing services must be professional so that maximum performance results. If the performance of nurses in basic services is maximized, the quality of the quality of health services will be better. Declining performance results in a sense of patient and family satisfaction, which will have an impact on the quality of hospital services. . Factors that influence the risk of decreased performance are workload, work stress and work motivation. The purpose of this study was to determine the effect of workload, work stress and work motivation on the performance of nurses in the inpatient installation of Dr. Sayidiman Magetan Hospital. The research design used was quantitative analytic with cross sectional approach. The sampling technique uses Proposinal Random Sampling with a sample of 100 respondents. Data were collected using a questionnaire, then analyzed using the ordinal regression test. The results showed, from the results of statistical tests stimulatively obtained p value of 0,000 <α = 0.05, meaning that all independent variables jointly influence the dependent variable. Statistical test results partially found that there was an influence between workload and work stress on nurses 'performance while, there was no effect between work motivation on nurses' performance, with p values ​​for each variable namely workload (p <0,000), work stress ( p <0.007), work motivation (p <0.862). Ordinal regression analysis shows work motivation is a variable that does not affect the performance of nurses with a value (p <0.862> 0.05). Nurse performance is influenced by workload factors, work stress and work motivation, so these aspects need to be managed well in the hope of getting better performance results and service quality